Ethylenediamine pretreatment to maximize fermentable sugar conversion from banana peel - Alasali, Usame; Azmi, Azlin Suhaida; Karaman, Isa; Mohammad, Zahangir Alam; Mohamad Puad, Noor Illi (2021)
The great demand for fermentable sugars derived from low-cost materials to produce several chemical products such as ethanol and lactic acid gave the lignocellulosic biomass considerable significance among other substrates. Alkaline pretreatment has been used widely to increase the enzymatic digestibility of fibers. However, this method encounters several problems like high chemical loading requirements and the irreversible adsorption of the chemicals on the surface of pretreated biomass, making the pretreatment process less effective. In contrast, using dilute ethylenediamine (EDA) would solve these problems. In this study, the fermentable sugar conversion was maximized from banana peel (BP) by optimizing EDA concentration (1-10%), pretreatment temperature (30-150oC) at ambient pressure and for 1 hour. X-ray Diffractogram analysis showed that the highest conversion of cellulose I to cellulose III (~20%) occurred after pretreating BP at 90oC with 5.5% EDA for 1 hour. Simultaneously, the crystallinity index decreased around 8% compared to raw BP. The Fourier Transform Infrared Spectroscopy analysis and Scanning Electron Microscope images proved the lignin removal and the cellulose content enhancement after the pretreatment. This study showed that abundant lignocellulosic wastes like BP could be pretreated with dilute EDA to increase their ability to be utilized by microorganisms for numerous fermentation processes.